Analisis Kepuasan Pengguna RME Menggunakan Metode EUCS di RSU Mardi Lestari Sragen - Alvina Rahmawati; Sri Wulandari; Resia Perwirani (Lembaga Pengembangan Kinerja Dosen, 2026)
A health information system that supports the improvement of service quality through digital patient data management is known as Electronic Medical Records (EMDR). The success of EMR implementation can be seen from the level of user satisfaction. Mardi Lestari General Hospital, Sragen, has implemented EMR in various service units, but user evaluation has never been conducted. This study aims to analyze EMR user satisfaction based on the dimensions of content, accuracy, format, ease of use, and timeliness using the End User Computing Satisfaction (EUCS) method. This study uses a descriptive qualitative method. Data were obtained through observation, semi-structured interviews, and source triangulation. Research informants were EMR users in outpatient, inpatient, and emergency units selected by purposive sampling. Data analysis was carried out through data reduction, data presentation, triangulation, and conclusion drawing. The results showed that users were generally satisfied with the use of EMR. The available information was assessed as appropriate to service needs, accurate, easy to understand, and supports work efficiency. The system was also able to provide information quickly to support patient care. However, several obstacles were still found, such as features that have not been optimally integrated, a fairly crowded display, and network disruptions that affect access speed. It can be concluded that the implementation of RME at RSU Mardi Lestari Sragen has provided satisfaction to users. However, system development is still needed, especially in feature integration, display improvements, and network quality improvements to support more optimal services.